2008
DOI: 10.1590/s1517-86922008000100001
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidantes, atividade física e estresse oxidativo em mulheres idosas

Abstract: Objetivo: Verificar a influência da suplementação de vitaminas antioxidantes na dieta de mulheres idosas que praticam exercícios físicos regulares, sobre o estresse oxidativo, indicadores da saúde física e risco de enfermidades cardiovasculares (ECV). Método: Foram observados dois grupos (S e C) de mulheres com idades entre 60 e 80 anos participantes de um programa de atividades físicas durante 58 semanas, com freqüência de três vezes por semana e duração de 50 a 55 minutos cada sessão. A dieta habitual do Gru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Several studies have evaluated the nutritional risk of elderly individuals, 5,7,[17][18][19][20][21] but only one study (using the MNA) assessed the risk of malnutrition in elderly patients with congestive heart failure. 22 The study observed "risk of malnutrition" in 71% of men and 70% of women, while 5% of men and 15% of women were classified as "malnourished", showing higher prevalence of risk of malnutrition compared to the rate observed in the present study (45% of men and 40% of women), and higher prevalence of "malnourished" compared to the rate observed in the present study (25% of men and 47% of women).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have evaluated the nutritional risk of elderly individuals, 5,7,[17][18][19][20][21] but only one study (using the MNA) assessed the risk of malnutrition in elderly patients with congestive heart failure. 22 The study observed "risk of malnutrition" in 71% of men and 70% of women, while 5% of men and 15% of women were classified as "malnourished", showing higher prevalence of risk of malnutrition compared to the rate observed in the present study (45% of men and 40% of women), and higher prevalence of "malnourished" compared to the rate observed in the present study (25% of men and 47% of women).…”
Section: Discussionmentioning
confidence: 99%
“…These changes can reduce quality of life and increase risk of both morbidity and mortality in this population group, predisposing the development of disease, notably cardiovascular pathologies. [3][4][5] Congestive heart failure (CHF) is the most frequent cause of hospitalization for cardiovascular disease, accounting for 2.6% of hospitalizations and 6% of deaths recorded by The Brazilian National Health System (SUS) in 2007. Moreover, the rate of in-hospital mortality varies with age, being higher in elderly individuals.…”
Section: Introductionmentioning
confidence: 99%
“…A literatura (REBELATTO et al, 2008), aponta que a prática regular de exercício físico, induz o estresse oxidativo e a peroxidação lipídica. Em situações fisiológicas, o oxigênio sofre redução pelo sistema citocromo-oxidase na mitocôndria, ocasionando uma redução tetravalente a água, com formação de moléculas de ATP, além de espécies reativas de oxigênio (POWERS; RADAK; JI, 2016).…”
Section: Variavéisunclassified